Experimental Study of an Aluminum-Polysilicon Thermopile for Implementation of Airflow Sensor on Silicon Chip - Subandi, Ayub; Idris, Irman; Ahmad, Adang Suwandi (ITB Journal Publisher, LPPM ITB, 2007)
A multi-directional airflow sensor has been realized. The essential part ofÂ theÂ consideredÂ sensorÂ isÂ aÂ thermopileÂ configuration,Â whichÂ enablesÂ the measurementÂ ofÂ flowÂ speedÂ andÂ flowÂ direction.Â TheÂ thermopileÂ isÂ aÂ series arrangementÂ ofÂ eightÂ thermocouples.Â AÂ thermocoupleÂ convertsÂ aÂ differenceÂ in temperatureÂ intoÂ anÂ electricalÂ signal,Â byÂ meansÂ ofÂ theÂ SeebeckÂ effect .Â The thermocouplesÂ areÂ madeÂ ofÂ aluminum-N-typeÂ polysiliconÂ junctions.Â The incomingÂ flowÂ isÂ heatedÂ andÂ theÂ degreeÂ ofÂ heatÂ transferÂ byÂ convectionÂ toÂ the flow, depends on the speed of the flow; the faster the flow the smaller the heat transfer,Â which leads to a smaller (Seebeck) outputÂ voltage ofÂ the thermopiles. AfterÂ signalÂ conditioningÂ -Â i.e.,Â filteringÂ andÂ amplificationÂ byÂ meansÂ ofÂ an amplification systemÂ -Â the electrical output signals of the thermopiles are further signal-processed by applying analog-to-digital signal conversion, so that finally the flow speed and the flow direction can be properly displayed on a computer screen. The measured values of the Seebeck coefficient or thermopower (S) were in the range of: 0.43 to 0.68 mV/K which are in good agreement with the values found in the literature: 0.5 to 0.7 mV/K. Moreover, itÂ was found that theÂ flow speedÂ Uï¥ isÂ proportionalÂ toÂ theÂ reciprocalÂ valueÂ ofÂ theÂ squareÂ ofÂ theÂ output voltage of the outgoing thermopile.